Physical, nutritional and functional quality of defatted coconut residue from four coconut (Cocos nucifera L.) varieties; as a dietary supplement for the food industry - Pathirana, H. P. D. T. Hewa; Lakdusinghe, W. Meththa Kumari; Yalegama, L. L. W. Chandi; Chandrapeli, C. A. Thamali Dhanushika; Marikkar, J. M. Nazrim (International Coconut Community Journal, 2025)
The value addition to the by-products enhances the profitability of the industry with a zero-waste concept. Defatted desiccated coconut flour (DCF) is a residue after the extraction of virgin coconut oil (VCO). This research aims to identify the effect of a variety of coconuts on the physical, nutritional and functional quality of DCF compared to whole wheat flour (WWF). Mature coconuts of four different varieties: Tall×Tall (TT), Ran Thambili (RT), San Ramon (SR), and Gon Thambili (GT) were used for the VCO extraction process by the cold press extraction followed by conversion of residue into flour (DCF). The average residue recovery is 15.33 ± 0.41% (p>0.05). The particle size of DCF is significantly higher than WWF, and only 23.16% of DCF is at the 250 µm level. The highest wettability (27.46±0.00 s) and swelling capacity (49.00±0.00 ml) have been identified in GT with a significantly (p